Regnase-1 overexpression as a novel gene therapy approach for pulmonary hypertension. (3rd October 2022) - Remes, A; Kasap, P; Schmiedel, N; Hille, S; Matzen, A; Michalewski, S; Laban, H; Hecker, M; Frey, N; Korff, T; Frank, D; Mueller, O J
Abstract: Introduction: Pulmonary hypertension (PH) is a chronic disease characterized by persistently increases pulmonary arterial pressure, leading on the long term to right ventricular overload and ultimately right heart failure. Until now, therapy focuses on alleviating symptoms and hence the development of a novel strategy for the treatment of this disease remains highly relevant. Purpose: The importance of pro-inflammatory cytokines in progression of PH has already been established. Interestingly, patients with increased plasma levels of inflammatory markers present with more severe disease. Regnase-1 is a newly identified endoribonuclease cleaving the mRNA of pro-inflammatory cytokines therefore diminishing their levels of expression. Hence, we hypothesize that regnase-1 overexpression in lung tissue can be translated into a novel therapeutic approach for PH. Methods: In vitro experiments were performed in human lung endothelial cells (HUVECs). For our in vivo study, mice were subjected to hypoxic conditions (10% O2) for 3 weeks. Regnase-1 overexpression was achieved in lung endothelial cells by transduction with targeted adeno-associated virus serotype 2 (AAV2-ESGHGYF), administered systemically by tail vein injection 3 days after exposure to hypoxia (early therapy approach). AAV2-EGFP treated mice served as controls. Right ventricular function was monitored by echocardiography and right ventricular systolic pressure was measured by right heart catheterization. The degree of pro-inflammatory cell infiltration was monitored by immunohistochemistry. Induction of fetal gene programme in the right ventricle was measured by real time qPCR. Fibrosis deposition in lung tissue was determined by Sirius Red staining of frozen sections. Results: Regnase-1 overexpression led to a significantly decreased level of hypoxia-induced pro-inflammatory cytokines in HUVECs. Importantly, we could show decreased regnase-1 levels in lung endothelial cells of mice subjected to hypoxia for 3 weeks. On the other hand, regnase-1 reintroduction led to a significant improvement in right ventricular function and decreased pulmonary pressure in mice placed under hypoxic conditions. Moreover, the described gene therapy approach induced normalization of fetal gene programme in the cardiac tissue and reduced pro-inflammatory cell infiltration in lungs. Additionally, we could determine mitigation of pulmonary extracellular matrix deposition and fibrosis development in mice receiving AAV2-regnase1 as compared to controls. Conclusion: AAV-mediated regnase-1 overexpression in lung endothelial cells results in amelioration of pathological events leading to PH in mice subjected to hypoxia, when the therapeutic AAV is delivered 3 days after disease induction. Further experiments will determine whether this method can be successful used for reversing already established PH. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DZHK